Population structure and spatial pattern of predominant tree species in a pine–oak mosaic mixed forest in the Qinling Mountains, China. Issue 1 (1st January 2017) - Kang, Haibin; Zheng, Yuying; Liu, Shutong; Chai, Zongzheng; Chang, Mingjie; Hu, Youning; Li, Gang; Wang, Dexiang
ABSTRACT: This study investigated a typical pine-oak mosaic mixed forest in the Qinling Mountains, China. In the sample plot, the population structure and spatial distribution of the stems were analyzed for the predominant species, to identify the mechanisms of species coexistence and successional trends of the forest. The population structures of all species were bimodally distributed, with young trees (DBH <1 cm) more abundant than older trees. The population structures of Quercus aliena var. acuteserrata was bimodal and rather continuous. However, Pinus tabuliformis and Pinus armandii were discontinuously bimodal, with distinct size deficiencies. Q. aliena var. acuteserrata trees were clumped throughout the plot, although those of P. tabuliformis and P. armandii were clumped at small scales. Notable negative spatial associations between Q. aliena var. acuteserrata and P. tabuliformis were found at almost scales. P. armandii and Q. aliena var. acuteserrata were negatively spatially associated at small scales but positively associated at large scales. Our findings suggest that interspecific competition gradually develops among the predominant tree species. The dynamics of the pine-oak mosaic mixed forest formed a mosaic distribution of uniformly mixed types, with the slow infiltration of Q. aliena var. acuteserrata populations that would eventually establish a pure stand.